Beyond the genomes of Fulvia fulva (syn. Cladosporium fulvum) and Dothistroma septosporum: New insights into how these fungal pathogens interact with their host plants. - Mesarich CH; Barnes I; Bradley EL; de la Rosa S; de Wit PJGM; Guo Y; Griffiths SA; Hamelin RC; Joosten MHAJ; Lu M; McCarthy HM; Schol CR; et al. (BSPP and John Wiley and Sons, Inc., 2023)
Fulvia fulva and Dothistroma septosporum are closely related apoplastic pathogens with similar lifestyles but different hosts: F. fulva is a pathogen of tomato, whilst D. septosporum is a pathogen of pine trees. In 2012, the first genome sequences of these pathogens were published, with F. fulva and D. septosporum having highly fragmented and near-complete assemblies, respectively. Since then, significant advances have been made in unravelling their genome architectures. For instance, the genome of F. fulva has now been assembled into 14 chromosomes, 13 of which have synteny with the 14 chromosomes of D. septosporum, suggesting these pathogens are even more closely related than originally thought. Considerable advances have also been made in the identification and functional characterization of virulence factors (e.g., effector proteins and secondary metabolites) from these pathogens, thereby providing new insights into how they promote host colonization or activate plant defence responses. For example, it has now been established that effector proteins from both F. fulva and D. septosporum interact with cell-surface immune receptors and co-receptors to activate the plant immune system. Progress has also been made in understanding how F. fulva and D. septosporum have evolved with their host plants, whilst intensive research into pandemics of Dothistroma needle blight in the Northern Hemisphere has shed light on the origins, migration, and genetic diversity of the global D. septosporum population. In this review, we specifically summarize advances made in our understanding of the F. fulva-tomato and D. septosporum-pine pathosystems over the last 10 years.
Keywords: Dothistroma needle blight (DNB); effector proteins; genome sequences; host susceptibility and resistance; pathogen diversity; secondary metabolites; tomato leaf mould; Ascomycota; Cladosporium; Pinus; Genome, Fungal; Host Microbial Interactions